Analisis Relevansi Syafaq Ahmar Terhadap Penentuan Akhir Waktu Shalat Magrib Perspektif Ilmu Falak - Addiessa Amalia Zainal Zainal; Mahyuddin Latuconsina; Muhammad Akmal (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims 1) to determine the beginning and end of the Maghrib prayer time, 2) to determine the criteria for the appearance of Syafaq Ahmar, 3) to determine the relevance of Syafaq Ahmar to the end of the Maghrib prayer time from the perspective of astronomy. This type of research is a qualitative research that is library research